(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The relationship between orthodox bioethics and bioethical legislative choices in the countries of Eastern Europe necessarily passes from the analysis of the relations that in these countries exist between the State and the Churches and the role played by orthodoxy, not only understood as religion but as a cultural factor and national identity. The study of the development of abortion legislation, starting from Soviet Russia, on the one hand, and the current regulations in those countries of surrogacy, on the other, make us understand how the relationship between bioethics and law is not only constantly evolving, but also how it reserves surprises, but without betraying completely the legacies of orthodoxy.